Self-assembled large scale metal alloy grid patterns as flexible transparent conductive layers - Mohl, Melinda (Sci Rep, 2015)
The development of scalable synthesis techniques for optically transparent, electrically conductive coatings is in great demand due to the constantly increasing market price and limited resources of indium for indium tin oxide (ITO) materials currently applied in most of the optoelectronic devices. This work pioneers the scalable synthesis of transparent conductive films (TCFs) by exploiting the coffee-ring effect deposition coupled with reactive inkjet printing and subsequent chemical copper plating. Here we report two different promising alternatives to replace ITO, palladium-copper (PdCu) grid patterns and silver-copper (AgCu) fish scale like structures printed on flexible poly(ethylene terephthalate) (PET) substrates, achieving sheet resistance values as low as 8.1 and 4.9 Ω/sq, with corresponding optical transmittance of 79% and 65% at 500 nm, respectively. Both films show excellent adhesion and also preserve their structural integrity and good contact with the substrate for severe bending showing less than 4% decrease of conductivity even after 10(5) cycles. Transparent conductive films for capacitive touch screens and pixels of microscopic resistive electrodes are demonstrated.